ARGON RELEASE SYSTEMATICS OF HYPOGENE AND SUPERGENE ALUNITE BASED ON PROGRESSIVE HEATING EXPERIMENTS FROM 100 TO 1000OC - Itaya T.; Arribas A.; Okada T. (My University, 1996)
Few minerals have as many different geological applications for K-Ar or 39Ar/40Ar dating as alunite (KAl3(SO4)2(OH)6), but a basic understanding of the systematics of argon release from this mineral is lacking. Progressive heating experiments from 100-1000°C at 100°C intervals were conducted in this study to obtain argon release patterns from hypogene and supergene alunite. The samples analyzed were selected from well understood deposits and are representative of the principal natural environments of acid-sulfate generation and related advanced argillic alteration and alunite formation. For gas extraction and purification, a low-blank metallic extraction-purification system used for dating silicates was complemented with a quartz-Pyrex glass line that included an external resistance furnace. The resulting patterns of argon release vs. temperature are well defined and similar for all the samples. Quantitative release of radiogenic 40Ar occurs during the dehydroxylation reaction of alunite at temperatures >400 and <700°C, in association with the first phase transformation of alunite during thermal decomposition to alum and alumina. This observation applies to alunites of different origin, regardless of characteristics such as grain size, crystal habit, growth temperature, and nature or origin of alunite-formation fluids. It applies as well to alunite treated chemically to remove small amounts of contaminant phases, such as illite. Argon released at <300°C is dominated by atmospheric argon adsorbed on the mineral surfaces, and Ar released at >800°C is mainly derived from the extraction system. The results indicate that the retentivity of Ar in fine-grained supergene alunite is similar to that of coarsely crystalline hypogene alunite. The data support the reliability of K-Ar dating of hypogene and supergene alunite and provide practical information to conduct routine high precision analyses.